Modifikasi Beton Fc 9,8 Mpa Menggunakan Abu Ampas Kopi - Shirfi Wimaya; Ahmad Ridwan; Sigit Winarto (Jurnal Manajemen Teknologi & Teknik Sipil, 2020)
Concrete is a construction material that is widely used in building structures. Cement is the main constituent of concrete whose needs are increasing. The expansion of coffee shops in Kediri City resulted in an increase in the volume of coffee grounds waste, which can be used as an alternative to cement. The purpose of this study was to determine the value of the slump test, compressive strength test, and test the absorption capacity of the addition of coffee grounds ash to the concrete sample specimen using a cylinder is measuring 15cm x 30cm with 5 pieces of concrete quality K-125 or equivalent to fc '9.8 Mpa. Slump test results with a percentage of 4%, 8%, 12%, namely 2.5 cm, 0.5 cm and 2.5 cm. The results of the concrete compressive strength test with a percentage of 4% obtained the results of the compressive strength fc '10.51 Mpa or equivalent to K125, a percentage of 8% produces a compressive strength of fc' 8.39 and a percentage of 12% produces a compressive strength fc '7.56 Mpa equivalent to K100. The water absorption test results for 28 days resulted in an average value of 0.32 kg, 0.25 kg, 0.15 kg, and 33 kg.Beton merupakan salah satu bahan konstruksi yang banyak digunakan pada struktur bangunan. Semen merupakan penyusun utama beton yang kebutuhannya semakin meningkat. Perluasan kedai kopi di Kota Kediri mengakibatkan peningkatan volume limbah ampas kopi yang dapat digunakan sebagai alternatif pengganti semen. Tujuan penelitian ini adalah untuk mengetahui nilai uji slump, uji kuat tekan, dan uji daya serap penambahan abu ampas kopi pada benda uji beton dengan menggunakan silinder berukuran 15cm x 30cm dengan kualitas beton sebanyak 5 buah. K-125 atau setara dengan fc '9.8 Mpa. Hasil uji slump dengan persentase 4%, 8%, 12% yaitu 2.5 cm, 0.5 cm dan 2.5 cm. Hasil uji kuat tekan beton dengan persentase 4% didapatkan hasil kuat tekan fc '10 .51 Mpa atau setara dengan K125 persentase 8% menghasilkan kuat tekan fc '8,39 dan persentase 12% menghasilkan kekuatan tekan fc '7,56 Mpa setara dengan K100. Hasil pengujian daya serap air selama 28 hari menghasilkan nilai rata-rata 0,32 kg, 0,25 kg, 0,15 kg, dan 33 kg.